PENGARUH SISTEM REKRUTMEN DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. KIMIA FARMA PLANT MEDAN - Wijaya, Muslim (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
This research heads for knowing the influences of the recruitment system to the job satisfaction of employees and the carrier development to the job satisfaction employee. The population of the these research are all employee of Imelda General Hospital. Simultantly this research head for knowing the influences of recruitment system and carrier development to the satisfaction employees.Keywords : recruitment, carrier development, job satisfaction,